Effect of Auricularia auricula fermentation broth on the liver and stomach of mice with acute alcoholism. Issue 1 (9th December 2020) - Yu, Xiaoting; Wang, Ruiying; Lai, Bin; Tan, Mingqian
Abstract : Auricularia auricula fermentation broth showed radical scavenging capability and protective effects on the liver and stomach of mice with acute alcoholism. Abstract : In this paper, the protective effect of Auricularia auricula ( A. auricula ) fermentation broth on the liver and stomach of mice with acute alcoholism was studied. The A. auricula fermentation broth was prepared by adding Bacillus subtilis, lactic acid bacteria, and Saccharomyces cerevisiae to A. auricula solution. The changes of physical and chemical indexes during the fermentation of A. auricula were monitored, and the results showed the content of polysaccharides and protein in the two kinds of fermentation broth after the fermentation was completed. Furthermore, the characteristic structures of active substances such as proteins, polysaccharides and phenolics were found in the A. auricula fermentation by structural analysis. Antioxidant activity test results showed that the A. auricula fermentation broth had a strong ability to scavenge 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radicals. Cell experiments showed that the fermentation broth of A. auricula could significantly enhance the activity of NRK cells and protect NRK cells from H2 O2 damage. Animal experiments showed that the A. auricula fermentation broth had protective effects on the liver and stomach of mice with acute alcoholism, and significantly reduced the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC) and triglycerides (TG) in serum. These results indicated that the A. auricula fermentation broth had protective effects on the liver and stomach of mice with acute alcoholism, and could be used as a potential functional food to prevent liver and stomach damage caused by acute alcoholism.